1995
DOI: 10.1080/10473289.1995.10467388
|View full text |Cite
|
Sign up to set email alerts
|

Leaching Dynamics Studies of Municipal Solid Waste Incinerator Ash

Abstract: An assessment of the short-and long-term hazards from municipal solid waste incinerator (MSWI) ash is made through the elemental analysis of 40 to 50 elements in the ash and leachates produced by several leaching procedures. The ash was analyzed using neutron activation analysis (NAA) and x-ray fluorescence (XRF). The leachates were analyzed using NAA and inductively-coupled plasma atomic emission spectroscopy (ICP). The leaching dynamics of an ash monofill were modelled with a series of extractions using simu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 23 publications
0
17
0
Order By: Relevance
“…Recent studies of heavy metal contents in similar types of residues report concentrations of the same order of magnitude of those obtained in this work. 10,24,27,29 APC residues compared with fly ashes are enriched in volatile elements such as Cd and Hg. This can be partially due to the efficiency improvement of APC systems.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies of heavy metal contents in similar types of residues report concentrations of the same order of magnitude of those obtained in this work. 10,24,27,29 APC residues compared with fly ashes are enriched in volatile elements such as Cd and Hg. This can be partially due to the efficiency improvement of APC systems.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have shown the presence of such toxic metals as Cd, Pb, Cr, Zn, Hg, and soluble salts, and have studied the leaching behavior of these types of wastes. 1,[7][8][9][10] Several works 11,12 have surveyed heavy metal distribution in APC residue as a function of particle size, showing that the most volatile elements, except Hg, tend to concentrate on the smallest particles. These results are in agreement with the assumption that IMPLICATIONS Improvements in flue gas cleaning by modern incinerators produce APC residues with higher metal solubility than fly ash.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous leaching tests have been developed worldwide, each characterized by different aims (research or regulatory controls) and different experimental parameters (pH, leachant, stirring device, time of extraction, etc.) [1,2,3,4,5,6]. Some research groups have been working on the design and study of extraction protocols aiming at the sequential solubilization of elements bound to the specific substrates making up fly ash and known to undergo changes in the yearly life cycle after deposition [7].…”
Section: Introductionmentioning
confidence: 99%
“…Other workers, using a different five-step extraction, demonstrated marked differences in contaminant speciation between MSW obtained from different composting facilities in the USA, emphasising the need for site-specific waste characterisation (He et al, 1995). Sequential extraction has also been used to assess the impact of MSW incinerator ash following disposal to landfill (Buchholz and Landsberger, 1995;Tan et al, 1997): pH was identified as the factor most strongly affecting both speciation and resultant metal concentrations in leachates. Speciation of Cd, Cr, Cu, Pb, V and Zn in fly ash from a variety of sources was described by Bodog et al (1996), whilst use of the approach has aided efforts to find means, including thermal treatment ( Wunsch et al, 1996) and addition of marine clay (Lim et al, 1997), of stabilising fly ash to leaching.…”
Section: 1021mentioning
confidence: 99%